Purification and separation of hydrophobic serum amyloid A precursor isoforms by a one-step preparative method - Ham, D; Karska-Wysocki, B (Journal of immunological methods, 2005)
The levels of two major serum amyloid A precursor isoforms, SAA1 and SAA2, which are associated with high-density lipoproteins (HDL) are increased during inflammation. The hydrophobic character and the small size difference--corresponding to just 0.8 kDa--between these two members of the SAA family hinder their separation and purification on a large scale by conventional methods. In the current work, both mouse SAA proteins were purified from HDL-SAA and acute-phase serum within 10 h in a one-step procedure using the high-resolution, continuous-elution preparative gel electrophoresis Prep-Cell system in combination with Tris/Glycine SDS-PAGE. Moreover, applying the Tris/Tricine system on the Prep-Cell resulted not only in purification of the SAA proteins, but also in their separation within 16 h. The SAA isoforms were freed from SDS using a Centricon concentrator and were identified using monoclonal antibodies. Optical density profile plots of gel protein or Western blot bands in combination with a colorimetric spectrophotometric protein assay showed that the recovery of the isoforms ranged from 38% to 60%. These results show that the preparative gel electrophoresis system Prep-Cell is a suitable device for separating SAA1 and SAA2 proteins in a simplified, convenient, and fast procedure, which can be applied on a small or large scale.
Keywords: Protein Precursors; Electrophoresis, Polyacrylamide Gel; elektroforéza v polyakrylamidovém gelu; Mice; sérový amyloid A; Silver Staining; Animals; barvení stříbrem; Research Support as Topic; protein - isoformy; hydrofobní a hydrofilní interakce; Hydrophobic and Hydrophilic Interactions; Serum Amyloid A Protein; myši; zvířata; proteinové prekurzory; finanční podpora výzkumu jako téma; Protein Isoforms